Neuropsychological intervention in the cognitive functioning of older adults with mild cognitive impairment (European Journal of Health Research, 2026)
Introduction: Mild cognitive impairment represents a high-risk state for progression to dementia, making neuropsychological interventions a promising therapeutic strategy. Objective: To evaluate the clinical utility of a neuropsychological intervention program on the overall cognitive functioning of older adults with mild cognitive impairment who attended the Center for Research on Longevity, Aging, and Health during 2022. Materials and methods: A pre-post quasi-experimental study with a single intervention group included 26 purposive older adults who participated in 12 sessions of cognitive training and activities of daily living, reality orientation therapy, and reminiscence therapy. Statistical analysis was performed using the Wilcoxon signed-rank test. Results: Although the change in the overall MoCA score was not statistically significant (p = 0.65), a relevant clinical impact was observed: 73% of the patients maintained or improved their cognitive performance. Improvements were identified in specific domains (executive functions, attention, and visuospatial skills), while memory proved to be the most resilient domain. In the functional sphere, 73.1% maintained their independence. A notable finding was that participants with hypertension showed significantly greater improvement in instrumental activities of daily living (p = 0.04). Conclusions: The evaluation of the neuropsychological program suggests that the intervention can contribute to the stabilization of cognitive and functional performance in older adults with mild cognitive impairment. Although no statistically significant changes were observed overall, most participants maintained or improved their performance, representing a preliminary indication of benefit. The heterogeneity in response indicates the need to adapt future interventions according to individual clinical profiles.
Keywords: mild cognitive impairment; neuropsychological intervention; older adults